Mauritania : First Review under the Three-Year Arrangement Under the Extended Credit Facility-Staff Report and Press Release. (IMF Staff Country Reports; Country Report ;, 2010)
Program implementation is satisfactory and economic activity is recovering in Mauritania. The budget preserves fiscal discipline and protects infrastructures and social spending. Greater flexibility in the exchange rate and an enhanced monetary policy framework will help build reserves. The structural program continues to focus on improving the business climate. The commitment for continued fiscal consolidation is commended by Executive Directors. This will help strengthen the country's resilience to external shocks, improve the country's prospects for mobilizing external support, sustain economic growth, create jobs, and reduce poverty.